Microsoft Azure Solutions Architect Expert (AZ-305) Cert Prep by Microsoft Press. - Hargreaves, Brett; Press, Microsoft (linkedin.com, 2024)
Review the core requirements for the AZ-305 exam. Discover how to design and build solutions in Azure and explore the options available to create scalable, secure systems.